Comprehensive performance assessment of a 12-MW grid-connected photovoltaic power plant - Bouroumeid, Yassine; Jbilou, Mokhtaria; Bechekir, Seyf Eddine; Nemmich, Said; Ghaitaoui, Essama Ahmed; Brahami, Mostefa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The increasing demand for electricity, driven by sustained population growth, has placed considerable pressure on Algeria’s power generation infrastructure to expand its output. In parallel, the sharp decline in the cost of solar photovoltaic (PV) electricity and the rising tariffs on conventional energy sources have intensified interest in PV-based electricity generation. Accordingly, precise evaluation of the annual and monthly performance of solar PV plants has become essential for the optimal design and deployment of new facilities. This study presents a comprehensive performance assessment of a 12 MW grid-connected photovoltaic power plant located in Sidi Bel Abbès, Algeria. Real-time operational data were collected over a one-year period, from January 1st to December 31st, 2023. Key performance indicators analyzed include energy output, final yield (Yf), and performance ratio (PR), among others. The plant delivered a total of 20,780.67 MWh to the grid in 2023. The final yield ranged from 3.25 to 5.88 kWh/kWp, while the performance ratio varied between 79% and 89.71%. The annual capacity factor was calculated to be 19.44%. These empirical results are compared against simulation outputs obtained using PVsyst and the Solar GIS-PV Planner tools.